2022
DOI: 10.1039/d1ew00811k
|View full text |Cite
|
Sign up to set email alerts
|

Sustainably closed loop recycling of hierarchically porous polymer microbeads for efficient removal of cationic dyes

Abstract: Herein, we designed and fabricated a hierarchically porous crosslinked polymeric microbead (PCP) with high density of functional groups for selective adsorption of cationic dyes from water. On account of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The successful carboxylation of PPF to prepare CPPF was determined by FT-IR and XPS spectroscopy. As shown in Figure a, the FT-IR spectrum of PPF displays the unique absorption peaks of epoxy groups at 849 and 918 cm –1 , confirming that PPF is mainly composed of PGMA polymers. After IDA modification, CPPF shows additional peaks at 1594 and 998 cm –1 corresponding to the CO bonds in IDA and the −OH groups .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The successful carboxylation of PPF to prepare CPPF was determined by FT-IR and XPS spectroscopy. As shown in Figure a, the FT-IR spectrum of PPF displays the unique absorption peaks of epoxy groups at 849 and 918 cm –1 , confirming that PPF is mainly composed of PGMA polymers. After IDA modification, CPPF shows additional peaks at 1594 and 998 cm –1 corresponding to the CO bonds in IDA and the −OH groups .…”
Section: Resultsmentioning
confidence: 72%
“…For instance, Hasan et al successfully removed harmful dyes using the carbohydrate polymeric turmeric powder as an adsorbent under neutral and alkaline circumstances . Iminodiacetic acid (IDA), a multifunctional group modified by PGMA, can achieve the ring opening of epoxy on PGMA through a straightforward amine–epoxy reaction, resulting in the formation of IDA groups with several teeth, including carboxylic acid, hydroxyl groups, and tertiary amines. In a pH-appropriate environment, this enables the produced IDA-modified PGMA to display significant electronegativity and superhydrophilicity with a high affinity for various types of contaminants. Additionally, Awual showed that adsorbents with secondary amine and tertiary amine structures, such as ligand-immobilized face composite adsorbent, have a synergistic impact on metal ions and achieve selective adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, to realize the adsorption and separation of certain harmful substances from water, hydrophilic groups such as sulfonic acid ( SO 3 H), carboxylic acid ( COOH), amino group ( NH 2 ), and so forth, are usually introduced into the structure of porous polymers. [15][16][17][18] For example, Yi et al prepared macroporous polyacrylic acid (PAA) hydrogels for adsorption of methylene blue via oil-in-water (O/W) Pickering HIPE templates. 19 Jurjevec et al synthesized functional macroporous amphiphilic polyelectrolyte monolithic structures with tunable structure and properties for dye adsorption via emulsion templates.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of technology and the large demand for textiles and printing, the industrial discharge is gradually increasing. These industrial wastewaters are highly variable and complex, which can contain suspended particles and refractory organic substances such as dyes. The complexity and variability of these wastewaters makes most commonly adopted single-step technologies fail to meet stringent waster regulations. To achieve complete removal of these pollutants, wastewater treatment facilities have to adopt a series of complicated processes that combine different technologies of adsorption, oxidation, , disinfection, and filtration. Therefore, given the rapidly expanding inventory of industrial wastewaters and increasing demands for high treatment efficiency for these complex wastewaters, it is urgent to find a viable and simple strategy to realize complete remediation of these pollutants from wastewater through a single-step treatment.…”
Section: Introductionmentioning
confidence: 99%